EFEKTIVITAS PELATIHAN METODE CERAMAH DAN DISKUSI KADER KESEHATAN UNTUK MENINGKATKAN PENGETAHUAN TENTANG KESEHATAN IBU DAN ANAK DI PUSKESMAS I BATURRADEN - Kurniawan, Arif; Gamelia, Elviera; Sistiarani, Colti (Kesmas Indonesia: Jurnal Ilmiah Kesehatan Masyarakat, 2017)
Maternal and child health problems is a major problem in rural of Baturaden I public health centers,Banyumas disctrict. Rural communities in the region have no access to maternal and child health information that is adequate, and the present lack of health information. This study aims to determine the effectiveness of training through lecture and discussion on the improvement of health worker knowledge about maternal and child health. This research is a quasi experimental study with a sample of 30 health cadres numbering . Analysis of the data used in this study is the paired t test to test for differences in knowledge before and after the intervention. The results showed an average value of knowledge about maternal and child health before training ( 9.31 ) and after training ( 10.0 ). The results showed an average value of knowledge about maternal and child health promotion before training (3.31 ) and after training ( 5.58 ). The statistical results showed no difference in the increase in knowledge about maternal child health, maternal and child health promotion knowledge before and after the intervention. Advice given is the advanced training of health promoters education on health workers with the method of simulation and mentoring. .